Decision support system for selection of the best teacher at SD Muhammadiyah 18 Medan using the analytical hierarchy process method - Josua Nainggolan; Johanes Apriadi Parlinggoman Sirait; Muhammad Fadlan Ikromi; Putri Ameliya Lubis; Debi Yandra Niska (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
A Decision Support System can be interpreted as a system that can and can provide solutions or capabilities both the ability to provide solutions or solve problems and the ability to communicate on semi-structured problemsHierarchy is a complex problem in a multi-level structure where the first level is the goal, followed by the level of problem factors, criteria, sub-criteria, alternatives, and so on down to the last level of alternatives. With a hierarchy, a complex problem can be translated into a collection of groups which are then organized into a hierarchical form so that the problem will appear more structured and systematicDecision Support System designed can be an alternative for SD Muhammadiyah 18 Medan and other schools in determining the best teacher. And with the establishment of a computerized system with the Analytical Hierarchy Process (AHP) method, the data processing process is faster and greatly minimizes errors and shortcomings in the calculation of values and also obtains maximum results. Obtained teacher data and the results of the value will be stored in the database so that if an error is found in the data entry and calculation results, the wrong data can be replaced through the database used. The final result can be concluded that the AHP method has given the best value recommendation to the teacher Syamsul Hidayat S, Pd with a value of 0.4473 with a percentage of 45%.